Lipid Dependence of Xanthophyll Cycling in Higher Plants and Algae - Goss, Reimund; Latowski, Dariusz (Frontiers in Plant Science, 2020)
The xanthophyll cycles of higher plants and algae represent an important photoprotection mechanism. Two main xanthophyll cycles are known, the violaxanthin cycle of higher plants, green and brown algae and the diadinoxanthin cycle of Bacillariophyceae, Xanthophyceae, Haptophyceae, and Dinophyceae. The forward reaction of the xanthophyll cycles consists of the enzymatic de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin or diadinoxanthin to diatoxanthin during periods of high light illumination. It is catalysed by the enzymes violaxanthin or diadinoxanthin de-epoxidase. During low light or darkness the back reaction of the cycle, which is catalysed by the enzymes zeaxanthin or diatoxanthin epoxidase, restores the epoxidized xanthophylls by a re-introduction of the epoxy groups. The de-epoxidation reaction takes place in the lipid phase of the thylakoid membrane and thus, depends on the nature, three dimensional structure and function of the thylakoid lipids. As the xanthophyll cycle pigments are usually associated with the photosynthetic light-harvesting proteins, structural re-arrangements of the proteins and changes in the protein-lipid interactions play an additional role for the operation of the xanthophyll cycles. In the present review we give an introduction to the lipid and fatty acid composition of thylakoid membranes of higher plants and algae. We introduce the readers to the reaction sequences, enzymes and function of the different xanthophyll cycles. The main focus of the review lies on the lipid dependence of xanthophyll cycling. We summarize the current knowledge about the role of lipids in the solubilisation of xanthophyll cycle pigments. We address the importance of the three-dimensional lipid structures for the enzymatic xanthophyll conversion, with a special focus on non-bilayer lipid phases which are formed by the main thylakoid membrane lipid monogalactosyldiacylglycerol. We additionally describe how lipids and light-harvesting complexes interact in the thylakoid membrane and how these interactions can affect the structure of the thylakoids. In a dedicated chapter we offer a short overview of current membrane models, including the concept of membrane domains. We then use these concepts to present a model of the operative xanthophyll cycle as a transient thylakoid membrane domain which is formed during high light illumination of plants or algal cells.